Standard Clause Problems in E-Commerce Based on Indonesian Civil Law - Hassanah, Hetty; Wahyudi, Wahyudi; Abdul Aziz, Norazlina (Jurnal Wawasan Yuridika, 2023)
Standard clauses are agreements determined by one party, usually a business actor. Standardized clauses are always part of e-commerce agreements, and this can be considered legal because it implements the principle of freedom of contract. This research aims to determine standard clauses in e-commerce in terms of civil law in Indonesia. The study is descriptive and utilizes normative juridical research through a legislative approach. Subsequently, secondary data collection techniques were employed using a literature review. The acquired data were then subjected to qualitative analysis. Based on the analysis in this research, it is known that standard clauses embody the principle of freedom of contract as regulated in Article 1338, paragraph (1) of the Code of Civil Law. However, they must still fulfill the legal requirements of the agreement as regulated in Article 1320 of the Code of Civil Law.